Effectiveness of Telemedicine Interventions in Improving Healthcare Access and Outcomes: A Systematic Review - Jasmin Ambas (Penelitian dan Pengembangan Ilmu, 2024)
This study examines the effectiveness of telemedicine interventions in improving access to health services and health outcomes in rural and remote areas of developing countries. Through the systematic literature review method, articles from international databases such as PubMed, Scopus, and Web of Science are collected and analyzed using the PRISMA framework. The results show that telemedicine can significantly increase the accessibility of healthcare services, reduce costs and travel time, and improve chronic disease management and overall patient health outcomes. The implications of this research support further adoption of telemedicine to reduce disparities in health services in remote areas.